2022
DOI: 10.7554/elife.81398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of orphan ligand-receptor relationships using a cell-based CRISPRa enrichment screening platform

Abstract: Secreted proteins, which include cytokines, hormones and growth factors, are extracellular ligands that control key signaling pathways mediating cell-cell communication within and between tissues and organs. Many drugs target secreted ligands and their cell-surface receptors. Still, there are hundreds of secreted human proteins that either have no identified receptors ('orphans') and are likely to act through cell surface receptors that have not yet been characterized. Discovery of secreted ligand-receptor int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…To test if we could predict receptors for orphan secreted ligands using the single-pass transmembrane library, we tested the screen using 15 ligands based on a previously curated library of potentially high-value orphan secreted proteins 15 ( Extended Data Table S3 ). Due to limited graphics processing unit (GPU) resources, we limited our test to binding partners that could be predicted using central processing units (CPUs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if we could predict receptors for orphan secreted ligands using the single-pass transmembrane library, we tested the screen using 15 ligands based on a previously curated library of potentially high-value orphan secreted proteins 15 ( Extended Data Table S3 ). Due to limited graphics processing unit (GPU) resources, we limited our test to binding partners that could be predicted using central processing units (CPUs).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, binding screens using an individual ligand applied to a receptor in solution are time-consuming, not applicable for all receptor types, and may lack the cellular environment necessary for posttranslational modifications or co-receptor binding 13,14 . Lastly, cell-based CRISPR screens have recently been utilized for the deorphanization of ligands, but are limited by the ability to gain sufficient receptor expression and the lack of expression of essential coreceptors 13,15 .…”
mentioning
confidence: 99%
“…A raw list of reported ubiquitin sites was obtained from PhosphoSitePlus (PSP; https://www.phosphosite.org) and matched to a curated list of the human membrane proteome (Siepe et al, 2022) to generate a master list of cell surface receptors with reported ubiquitination sites.…”
Section: Methodsmentioning
confidence: 99%
“…A raw list of reported ubiquitin sites was obtained from PhosphoSitePlus (PSP; https://www. phosphosite.org) and matched to a curated list of the human membrane proteome 65 to generate a master list of cell surface receptors with reported ubiquitination sites.…”
Section: Curation Of the Human Ubiquitin Cell Surfacementioning
confidence: 99%